(untitled) (Research, Society and Development, 2020)
Objective: To trace the epidemiology of morbidity and mortality and public spending due to Renal Insufficiency in Brazil between 2014 and 2019. Methodology: This is a quantitative, ecological and descriptive study, based on data collected in the Hospital Information System. The variables were selected: number of hospitalizations, gender, age group, race/color, deaths, mortality rate and costs of hospital services spent by the Renal Insufficiency in the regions of Brazil. The data were analyzed using simple descriptive statistics and presented using tables and graphs built by the Microsoft Office Excel program. Results: 649.102 cases of hospitalizations for Renal Insufficiency were reported. Comparing the years of study, 2019 had a higher number of hospitalizations and deaths due to Renal Insufficiency. It was observed that, during the period from 2014 to 2019, there was a higher prevalence in the Southeast (45,68%), male gender (56,76%), between 60-69 years (22,20%) and self-declared whites (36,20%). There were 82.948 deaths, of which 47,05% occurred in the Southeast, and mortality of 12,78%, with a higher rate in the North (13,95%.). There was a financial impact of more than R 1,9 billion. Conclusion: In addition to interfering with quality of life, changing family dynamics and predisposing to death, Insufficiency Renal implies high public spending. It is necessary to plan public policies aimed at prevention and health promotion, as well as strategies that allow users access to treatments.